Paracrine interactions of basic fibroblast growth factor and interleukin-6 in multiple myeloma - Bisping, Guido; Leo, Regine; Wenning, Doris; Dankbar, Berno; Padró, Teresa; Kropff, Martin; Scheffold, Christian; Kröger, Matthias; Mesters, Rolf M.; Berdel, Wolfgang E.; Kienast, Joachim (Blood, 2003)
Myeloma cells express basic fibroblast growth factor (bFGF), an angiogenic cytokine triggering marrow neovascularization in multiple myeloma (MM). In solid tumors and some lymphohematopoietic malignancies, angiogenic cytokines have also been shown to stimulate tumor growth via paracrine pathways. Since interleukin-6 (IL-6) is a potent growth and survival factor for myeloma cells, we have studied the effects of bFGF on IL-6 secretion by bone marrow stromal cells (BMSCs) and its potential reverse regulation in myeloma cells. Both myeloma-derived cell lines and myeloma cells isolated from the marrow of MM patients were shown to express and secrete bFGF. Cell-sorting studies identified myeloma cells as the predominant source of bFGF in MM marrow. BMSCs from MM patients and control subjects expressed high-affinity FGF receptors R1 through R4. Stimulation of BMSCs with bFGF induced a time- and dose-dependent increase in IL-6 secretion (median, 2-fold;P< .001), which was completely abrogated by anti-bFGF antibodies. Conversely, stimulation with IL-6 enhanced bFGF expression and secretion by myeloma cell lines (2-fold;P= .02) as well as MM patient cells (up to 3.6-fold; median, 1.5-fold;P= .002). This effect was inhibited by anti–IL-6 antibody. When myeloma cells were cocultured with BMSCs in a noncontact transwell system, both IL-6 and bFGF concentrations in coculture supernatants increased 2- to 3-fold over the sum of basal concentrations in the monoculture controls. The IL-6 increase was again partially, but significantly, inhibited by anti-bFGF. The data demonstrate a paracrine interaction between myeloma and marrow stromal cells triggered by mutual stimulation of bFGF and IL-6.